Real-time signal processing for fetal heart rate monitoring - Ibrahimy, Muhammad Ibn; Ahmed, Firoz; Mohd Ali, M. A.; Zahedi, Admond (IEEE, 2003)
An algorithm based on digital filtering, adaptive thresholding, statistical properties in the time domain, and differencing of local maxima and minima has been developed for the simultaneous measurement of the fetal and maternal heart rates from the maternal abdominal electrocardiogram during pregnancy and labor for ambulatory monitoring. A microcontroller-based system has been used to implement the algorithm in real-time. A Doppler ultrasound fetal monitor was used for statistical comparison on five volunteers with low risk pregnancies, between 35 and 40 weeks of gestation. Results showed an average percent root mean square difference of 5.32% and linear correlation coefficient from 0.84 to 0.93. The fetal heart rate curves remained inside a 5-beats-per-minute limit relative to the reference ultrasound method for 84.1% of the time